Effects of ginseng dietary supplementation on a high-Fat diet-induced obesity in C57BL/6 Mice - Jia-Ni Lin; Pei-Sheng Lee; Nai-Wen Mei; An-Chin Cheng; Roch-Chui Yu; Min-Hsiung Pan (Food Science and Human Wellness)
Excess caloric intake increases the amount of adipose tissue and contributes to metabolic disorders in disrupted metabolic homeostasis. This study aimed to investigate the anti-obesity effects of ginseng and the alternation of gut microbiota composition in high-fat diet (HFD)-induced obesity. The results showed that HFD treatment influenced body weight gain, adipose tissue accumulation and biochemical parameter changes. Compared to the HFD group, ginseng supplementation of HFD-fed mice decreased body weight, adipose tissue mass, total cholesterol (T-CHO) and high-density lipoprotein (HDL)/low-density lipoprotein (LDL) ratio. To analysis the alterations of gut microbiota, ginseng in dietary supplements decreased Firmicutes abundance and increased Bacteroidetes abundance. Taken together, these findings suggest ginseng may modulate the energy storage and alter gut microbiota composition. Keywords: Ginseng, High-fat diet, Obesity, Gut microbiota